Combination of Prostate Cancer Antigen 3 (PCA3), Sarcosine, Glypican-1 (GPC1), Urokinase Plasminogen Activator Receptor (uPAR), and Thymidine Kinase 1 (TK1), and T2WI and DWI Radiomics Model for Distinguishing Benign Prostatic Hyperplasia, Prostate Cancer: - - Yang, Fan; Guo, Wei; Sun, Siqin; Huang, Yanan (Journal of Medical Biochemistry, 2025)
-
Keywords: -